The Towitta tragedy : the true story of the Bertha Schippan murder - Dutschke, Richard ([Port Adelaide, South Australia] : Richard Dutschke, 2017)
This story recounts the inquest into the murder of Bertha Schippan on 1 January 1902. Her elder sister, Mary, was charged with the murder, but she was found not guilty. At the time, the news surrounding the murder and trial captivated the nation.
Keywords: Schippan, Bertha, -- 1888-1902.; Schippan, Mary, -- 1878-1919.; Murder -- South Australia -- Towitta; Murder investigation -- South Australia -- Towitta; Trials (Murder) -- South Australia -- Towitta; Australian